Validity of Digital Signature Evidence as Valid Evidence in Civil Procedure Law - Neilpon Yulinar Marquez; Hono Sejati; Mohamad Tohari (Universitas Ekasakti, 2024)
Indonesia is entering a globalization era that drives technological advancements and business activities towards greater efficiency, particularly in the form of e-commerce. The use of Digital Signatures in its development is starting to shift the dominance of conventional signatures in agreements typically made on paper. Based on civil procedural law systems, judges are bound by valid evidence, implying that judicial decisions are limited by the evidence regulated by the law (HIR/RGB). This study adopts a doctrinal approach, examining law based on legislative regulations and legal concepts, and utilizing various data sources such as primary, secondary, and tertiary legal documents. Data collection methods include legal literature, legislative regulations, scientific literature, and relevant internet information on the discussed topic. The research findings indicate that a digital signature is not a replica of a conventional signature scanned using a scanner, but rather utilizes cryptographic techniques. The principle of lex specialis derogat legi generali states that the use of digital signatures in Civil Procedural Law holds a legal equivalence to authentic deeds.